The process of identifying key uncertainties in the orthotics and prosthetics education foresight - Taheri Alireza; Changiz Tahereh; Tofighi Shahram (Wolters Kluwer Medknow Publications, 2019)
INTRODUCTION: Medical sciences effects on people's health; therefore, it is necessary to identify all threats, opportunities, and challenges in its policy and planning particularly in the education field. The orthotics and prosthetics (O and P) field of study has great importance alongside other rehabilitation sciences due to its preventive status, therefore, the purpose of this study is to investigate the role of key factors and, subsequently, identifying uncertainties to compile and plot a bright and planned future for O and P education system. MATERIALS AND METHODS: At first, the key factors seemed to be influential improving the education and training quality of O and P students, were identified, weighted and ranked. All these steps were based on documentations and opinions of elites and deans of O and P through a semi-structured interview. Then, the final list of key factors and extracted drivers was placed and analyzed in cross-impact matrix by MicMac software. RESULTS: Among the initial list of key factors and drivers which identified 45 elements; 19 key factors and drivers scored the highest. Among 238 evaluable relationships in the cross-impact matrix, 123 relationships (51.6% of total matrix volume) are 0, which means that factors do not affect each other and are not affected either. Two key factors were identified as critical uncertainties out of 19 key factors. CONCLUSION: Achieving education development without a dynamic and active planning system is not possible. "Community-based education" and "government financial support" were identified as critical uncertainties of O and P future education system.